THE EFFECT OF GIVING STARFRUIT LEAF EXTRACT IN DRINKING WATER ON THE PERFORMANCE OF QUAIL (Coturnix coturnix japonica) AGE 1-5 WEEKS - M. I., Alghozali; Wirapartha, M.; Dewi, G. A. M. K. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This study was conducted to determine the effect of giving starfruit leaves extract in drinking water on the performance of quail (Coturnix coturnix japonica) aged 1-5 weeks. This research was conducted in the Sesetan Teaching Farm and Poultry Livestock Laboratory, Faculty of Animal Science, Udayana University, for 5 weeks. The research design was used a completely randomized design (CRD) consisting of 4 treatments and 4 replications, each replication consisting of 4 quails. This study used 64 quails (Coturnix coturnix japonica) aged 1 week. The treatments are drinking water without starfruit leaf extract as a control (A). Provision of drinking water with 2% (B), 4% (C), 6% (D) starfruit leaves extract as treatment B, C, and D. The observed variables was initial body weight, water consumption, final body weight, body weight gain, feed consumption, feed conversion. The data obtained were analyzed by means of variance, if there was a significant difference (P <0.05), then continued with Duncan's multiple distance test. The results showed that each variable initial weight, final weight, body weight gain, ration consumption, ration conversion, drinking water consumption treatment 2%, 4%, 6% obtained results that were not significant (P> 0.05). Based on the results of the study, it can be concluded that giving wuluh starfruit leaf extract (Averrhoa bilimbi L) by giving 2%, 4% and 6% in drinking water did not affect initial body weight, final body weight, body weight gain, ration consumption, ration conversion, drinking water consumption in quail (Coturnix coturnix japonica) aged 1-5 weeks.